2005
DOI: 10.1002/mrd.20387
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic and epigenetic aberrations inDnmt3L-deficient male germ cells

Abstract: The DNA methyltransferase-like protein Dnmt3L is necessary for the establishment of genomic imprints in oogenesis and for normal spermatogenesis (Bourc'his et al., 2001; Hata et al., 2002). Also, a paternally imprinted gene, H19, loses DNA methylation in Dnmt3L-/- spermatogonia (Bourc'his and Bestor, 2004; Kaneda et al., 2004). To determine the reason for the impaired spermatogenesis in the Dnmt3L-/- testes, we have carried out a series of histological and molecular studies. We show here that Dnmt3L-/- germ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 28 publications
5
73
0
Order By: Relevance
“…Rather, more importantly, the down-regulation of methylation of CCGG sites may be a possible trigger of induction of germ cell apoptosis in premeiotic germ cells. In agreement with our findings, it is already known that treatment with 5-aza-2'-deoxycytidine (Kelly et al 2003) and mutation of Dnmt3L gene (Hata et al 2006), both of which induce a reduction or loss of DNA methylation in mouse testis, resulted in histological anomalies and germ cell loss in mouse testis. Koji T et al,Page 18 The present results also indicated that the level of methylation at CCGG sites in germ cells was generally higher than that in somatic cells like Sertoli cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Rather, more importantly, the down-regulation of methylation of CCGG sites may be a possible trigger of induction of germ cell apoptosis in premeiotic germ cells. In agreement with our findings, it is already known that treatment with 5-aza-2'-deoxycytidine (Kelly et al 2003) and mutation of Dnmt3L gene (Hata et al 2006), both of which induce a reduction or loss of DNA methylation in mouse testis, resulted in histological anomalies and germ cell loss in mouse testis. Koji T et al,Page 18 The present results also indicated that the level of methylation at CCGG sites in germ cells was generally higher than that in somatic cells like Sertoli cells.…”
Section: Discussionsupporting
confidence: 93%
“…Kelly et al (2003) reported that the use of Koji T et al,Page 5 5-aza-2'-deoxycytidine, a cytidine analogue known to decrease the level of DNA methylation, results in histological anomalies in testis. Moreover, DNA methyltransferase-like protein (Dnmt3L) homozygous mutant mice, which exhibit low methylation of DNA in testis, are infertile (Bourc'his et al 2001;Hata et al 2002) and are subject to meiotic aberrations with the appearance of apoptosis-like germ cells (Bourc'his and Bestor 2004;Hata et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of all the Dnmts, the role of Dnmt3L in transposon silencing has been described in the most detail. Dnmt3L lacks catalytic activity but is required for transcriptional repression, as well as for DNA methylation of the LTR-class IAP elements and the non-LTR class LINE-1 elements (long interspersed elements-1) in the male germline [114][115][116]. Again, methylation of H3K9 and DNA seem to be linked in this context.…”
Section: Reviewmentioning
confidence: 99%
“…Dnmt3L is a known partner of the de novo methyltransferase Dnmt3a [122][123][124] and, as such, might be involved in the establishment of DNA methylation patterns in the male germline. The strong resemblance among dnmt3l, miwi2 and mili phenotypes [45,86,[114][115][116]125] suggests that these genes all act in de novo methylation of transposon sequences.…”
Section: Reviewmentioning
confidence: 99%
“…2003;Bourc'his & Bestor 2004;Dodge et al . 2005;Hata et al . 2006), indicating that CpG methylation plays a fundamental role in basic cellular functions of mammalian cells.…”
Section: Introductionmentioning
confidence: 99%